INVESTIGATION OF BILINGUALISM COMMUNITIES: LANGUAGE TEACHING AND LEARNING IN BILINGUALISM CLASSROOM - Musahroh; Chairuddin; Iin Rachmawati (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
The study aims to know the kinds of bilingualism classrooms. The research design of the study was qualitative which focuses on a case study. This study focused on Colin’s theory about the kinds of bilingualism programs, they are bilingual programs, structured immersion, enrichment programs, and transitional programs. The data were obtained by observing the teacher and students in the videos teaching-learning process in bilingualism classroom by making a transcript. The result of the research finding revealed that there are only three kinds of bilingualism program of videos, the first bilingual program, second enrichment program, and the third transitional program.